2003
DOI: 10.1152/ajpregu.00269.2003
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine-induced cardiac hypertrophy: influence of adrenergic nervous system versus renin-angiotensin system on myocyte remodeling

Abstract: -The present study assessed the possible involvement of the renin-angiotensin system (RAS) and the sympathetic nervous system (SNS) in thyroxine (T 4)-induced cardiac hypertrophy. Hemodynamic parameters, heart weight (HW), ratio of HW to body weight (HW/BW), and myocyte width were evaluated in absence of thyroid hormone (hypothyroidism) and after T 4 administration. Male Wistar rats were used. Some were subjected to thyroidectomies, whereas hyperthyroidism was induced in others via daily intraperitoneal inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 34 publications
7
73
0
10
Order By: Relevance
“…Additionally, abnormal TH signaling͞metabolism is reported in both heart disease and after cardiopulmonary bypass surgery (5, 7). Thus, TH therapy has been advocated for treating cardiac disease (12,13), although clear benefit has been difficult to demonstrate, particularly with chronic use, possibly because of adverse extracardiac effects of TH (5,27). The response of our D2-overexpressing mice to AB supports the conclusion that cardiac-restricted T3 production by D2 protects against deterioration of heart function induced by pressure overload.…”
Section: Effects Of D2 Expression On Cardiac Function and Ca 2؉ Cyclingsupporting
confidence: 57%
See 2 more Smart Citations
“…Additionally, abnormal TH signaling͞metabolism is reported in both heart disease and after cardiopulmonary bypass surgery (5, 7). Thus, TH therapy has been advocated for treating cardiac disease (12,13), although clear benefit has been difficult to demonstrate, particularly with chronic use, possibly because of adverse extracardiac effects of TH (5,27). The response of our D2-overexpressing mice to AB supports the conclusion that cardiac-restricted T3 production by D2 protects against deterioration of heart function induced by pressure overload.…”
Section: Effects Of D2 Expression On Cardiac Function and Ca 2؉ Cyclingsupporting
confidence: 57%
“…Prolonged TH treatment has been shown to impair heart function, possibly because of (peripheral) extracardiac effects (14,27,28). As shown in Tables 1 and 2 (see also Table 3, which is published as supporting information on the PNAS web site), not only was deterioration of heart function not observed, but cardiac contractility and Ca 2ϩ transients remained elevated in Bin-Off mice 9 weeks after being withdrawn from DOX compared with Con-Off mice.…”
Section: Effects Of D2 Expression On Cardiac Function and Ca 2؉ Cyclingmentioning
confidence: 94%
See 1 more Smart Citation
“…A growing body of evidence indicates that the renin-angiotensin system (RAS) has a critical role in the development of cardiac hypertrophy found in hyperthyroidism and the local RAS, present in the cardiomyocytes, is directly implicated in this process (Diniz et al 2009, Carneiro-Ramos et al 2010. In this sense, the contribution of the RAS in this pathological condition has been demonstrated by several studies reported in the literature, which showed that AT1R receptor blockade and angiotensin-converting enzyme inhibition attenuate or prevent the development of cardiac hypertrophy induced by THs (Kobori et al 1997, Asahi et al 2001, Basset et al 2001, Hu et al 2003, Pantos et al 2005.…”
Section: Introductionmentioning
confidence: 95%
“…Ainda, estudos demonstraram que ratos hipertiroideos apresentam aumento da síntese de renina com conseqüente elevação dos níveis plasmáticos de Ang II, independente da participação do sistema nervoso simpático (Kobori, et al, 1997). Neste sentido, Hu, et al, (2003) mostraram que a administração de inibidores do SRA foi capaz de prevenir o desenvolvimento da hipertrofia cardíaca induzida pelo T4, confirmando a interação entre estes dois sistemas hormonais (Hu, et al, 2003).…”
Section: Sistema Renina Angiotensina E Hormônio Tiroideanounclassified